Production optimization oriented to value-added: from conceptual to a simulation case study. Issue 1 (October 2021) - Pérez, S; Gallego, S; García, M
Abstract: Management in companies today faces a true paradigm shift, characterized by a growing optimization of global value-added structures. To pursue this goal, lean philosophy is used as it allows applying sustainable improvements to the processes of a company, focusing on the value of the process and eliminating if possible or minimizing all those activities or tasks that when executed are not beneficial, that is, they do not add value. The research pursues to design and apply a systematic methodology to improve efficiency of a manufacturing plant increasing the value-added towards the end-customer. The objective of the work is to carry out an analysis of the manufacturing process of charged detonators to be potentially applied for other sectors. With the development of this work, it is described how it is possible to analyze, assess and implement improvement tools in manufacturing systems with a long tradition and that to date have not needed to improve their processes significantly due to market dynamics such as manufacturing of detonators. Moreover, a work methodology for optimizing manufacturing plants based on the proposed tools can be applied to other sectors.